AN ANALYSIS ON THE SECONDARY SCHOOL STUDENTS BURNOUT IN TERMS OF ACADEMIC SELF-EFFICACY, PARENTAL MONITORING, SOCIAL SUPPORT AND LEISURE TIME ACTIVITIES - (:unkn) unknown (My University, 2018)
Studies emphasize that school burnout is more intense in secondary and high school educationwhere choices related to the future and expectations become significant in addition to thedevelopmental problems. This study was carried out based on the opinion that expectations andanxiety about the importance of preparation and high performance can cause school burnout instudents from the 6th grade to the end of the 8th grade. In this context, the secondary schoolstudents’ burnout was examined in terms of academic self-efficacy, parental monitoring, socialsupport, leisure activities and demographical characteristics in the study. 396 students from the6th, 7th, and 8th grade of secondary school in İstanbul province, Kadıköy district participated inthis study. The study was designed in a descriptive research model and the data were analyzed inthe SPSS program by using t test, variance and correlation analysis techniques. The data of thestudy was obtained using School Burnout Scale, Academic Self-Efficacy Scale, Parental MonitoringScale, Child and Adolescent Social Support Scale and personal information form. The correlationanalysis show that there were a significant positive association between Burnout School andAcademic Self-Efficacy, (r(396) = .44, p=.000), between Burnout School and Frequency ofperception, (r(396) = .32, p = .000), and between Burnout School and importance, (r(396) = .34,p=.000), It was found that the level of burn out was higher in female students compared to themale students and parental monitoring was at different dimensions for female and malestudents. There was also a significance in academic self-efficacy when the education level of themother increases, and in feeling of insufficiency and academic self-efficacy when the educationlevel of father increases. Also there was a significant difference found in terms of age, grade,family employment status, academic achievement and leisure activities (p<0.05).
Keywords: Arkeoloji; Sanat; Coğrafya; Tarih; Dil ve Dil Bilim; Hukuk; Müzik; Felsefe; Sosyoloji